Proyecto de la factibilidad de la creación de un complejo turístico en el - Lucín, Alexis (2010)
This Project emerge as the needed that Santa Lucia`s corner, in fact that actually hasn`t a place where the kids and people in general will enjoy of many variety of green areas healthy recreation and many other attractive touristics of the people interesting. With the finality to know the opinion of the poblation, we realized a market`s investigation to the citizens of the corner and the result that we obtain was very interesting, the pilot inquiry showed 90% of the citizens wants a Touristic Complex in their corner, but the other 10% was not. This confirm that the market´s investigation realized for our group objective that show that the Touristic Resort RIBERAS DEL RIO SANTA LUCIA, will have the acceptation and will be located in Morochal at the beginning of the corner. In other to obtain a big market`s participation we selected an strategy user – oriented, highlighting the benefits that offer the project, which are the followings: Excellent and comfortable structure, quality care and over security. You will also see in this